Compensation patterns for healthcare workers in British Columbia, Canada. Issue 6 (18th November 2008) - Alamgir, H; Siow, S; Yu, S; Ngan, K; Guzman, J
Abstract : Objectives: This report examines relationships between the acceptance of compensation claims, and employee and workplace characteristics for healthcare workers in British Columbia, Canada to determine suitability of using only accepted claims for occupational epidemiology research. Methods: A retrospective cohort of full-time healthcare workers was constructed from an active incident surveillance database. Incidents filed for compensation over a 1-year period were examined for initial claim decision within a 6-month window relative to sub-sector of employment, age, sex, seniority, occupation of workers, and injury category. Compensation costs and duration of time lost for initially accepted claims were also investigated. Multiple logistic regression models with generalised estimating equations (GEEs) were used to calculate adjusted relative odds (ARO) of claims decision accounting for confounding factors and clustering effects. Results: Employees of three health regions in British Columbia filed 2274 work-related claims in a year, of which 1863 (82%) were initially accepted for compensation. Proportion of claims accepted was lowest in community care (79%) and corporate office settings (79%) and highest in long-term care settings (86%). Overall, 46% of claims resulting from allergy/irritation were accepted, in contrast to 98% acceptance of claims from cuts and puncture wounds . Licensed practical nurses had the lowest odds of claims not accepted compared with registered nurses (ARO (95% CI) = 0.55 (0.33 to 0.91)), whereas management/administrative staff had the highest odds (ARO = 2.91 (1.25 to 6.79)) of claims not accepted. A trend was observed with higher seniority of workers associated with lower odds of non-acceptance of claims. Conclusions: Analysis from British Columbia's healthcare sector suggests variation in workers' compensation acceptance exists across sub-sectors, occupations, seniority of workers, and injury categories. The patterns observed, however, were independent of age and sex of workers. Results suggest that when using workers' compensation datasets, local adjudication regulations and factors associated with acceptance of claims should be taken into consideration.